Oral health care for older persons with Alzheimer&s disease: considerations about treatment planning and caregiver involvement - Raquel de Oliveira Araújo; Ricardo Guimarães Fischer; Roberto Alves Lourenço (Brazilian Society of Geriatrics and Gerontology, 2023)
Alzheimer's disease (AD) is a neurodegenerative and progressive disease that predominantly affects women and has no cure. Obstacles to the dental care of people with AD differ in each phase, but the dental surgeon should remember to include the caregivers, formal or informal, in the treatment. Some skills need to be considered in the planning process, and dental health indices can be very helpful for the professional to assess the patient's ability to undergo treatment and how the older person can benefit from it. The dental surgeon should evaluate each person's specific needs so that personalized oral hygiene protocols can be established. The suggested adaptations must be by the reality of the older adult with AD, the family context, and daily routine, and they must contemplate the information provided by the caregiver. In this article, we invite the dental surgeon to understand the continuum of AD to properly plan treatment, considering the individual's limitations, future perspectives, and safety, always keeping the older adult free of oral infections and comfortable with his or her oral health condition.